Temporal trends and gender differentials in causes of childhood deaths at Ballabgarh, India - Need for revisiting child survival strategies - Krishnan Anand; Ng Nawi; Kapoor Suresh K; Pandav Chandrakant S; Byass Peter (BMC, 2012)
Abstract Background Relating Information on causes of deaths to implementation of health interventions provides vital information for program planning and evaluation. This paper from Ballabgarh Health and Demographic Surveillance System (HDSS) site in north India looks at temporal trends and gender differentials in the causes of death among under-five children. Methods Data on causes of death for 1972-74, 1982-84, 1992-94, 2002-04 were taken from existing HDSS publications and database. Physicians' assigned causes of death were based on narratives by lay health worker till 1994 and later by verbal autopsy. Cause Specific Mortality Fractions (CSMF) and Cause Specific Mortality Rates (CSMR) per 1000 live births were calculated for neonatal (<1 month) and childhood (1-59 months) period. Gender difference was estimated by calculating ratio of CSMR between girls and boys. Available information on coverage of childhood interventions in the HDSS was retrieved and compiled. Results The CSMF of prematurity and sepsis was 32% and 17.6% during neonatal period in 2002-04. The share of infections in all childhood deaths decreased from 55.2% in 1972-74 to 43.6% in 2002-04. All major causes of mortality (malnutrition, diarrhea and acute lower respiratory infection) except injuries showed a steep decline among children and seem to have plateued in last decade. Most of disease specific public health interventions were launched in mid eighties. . Girls reported significantly higher mortality rates for prematurity (RR 1.52; 95% CI 1.01-2.29); diarrhea (2.29; 1.59 - 3.29), and malnutrition (3.37; 2.05 - 5.53). Conclusions The findings of the study point out to the need to move away from disease-specific to a comprehensive approach and to address gender inequity in child survival through socio-behavioural approaches.